Healthy Narratives: the story in health promotion and stroke prevention - Ortiz Sánchez, Diana (2023)
Strokes also known as CVA, have increased in the last 20 years, it is expected that, worldwide, by the year 2030 it willbe present in 5 million people as a cause of death, the projection has been made with ischemic stroke, considered themost common (Fan, J., Li, X., Yu, X., Liu, Z., Jiang, Y., Fang, Y., y Xiong, L.,2023).The story “Something happens tograndma” is a pedagogical proposal developed for the promotion of healthy habits and prevention of CVA, the use ofthe story as an important psychoeducational tool for health promotion and disease prevention has been demonstrated(Babarro and Lacalle, 2018; Bravender, Rusell, Chung, & Armostrong 2010; Dupont, 1993; Franzini & De Santis, 2011;Pérez Ordóñez, 2019; Redondo, Gómez, Fabregat, & Camas, 2009; Rivera Daza, 2019; Jauregui, Martínez, Montes,& Martínez, 2020). The proposal has as its theoretical basis the processes described by the Transtheoretical Model ofChange in its first two stages, Precontemplation and Contemplation, by providing simple and specific information onCerebrovascular accidents. The application of the didactic material in story format can take place in different contexts,both in classrooms, childcare centers, clinics and hospitals, and the scope and impact would be reflected, to a greater orlesser extent, depending on the use of this material.